2013
DOI: 10.1128/ec.00129-13
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of an AP-1-Like Transcription Factor, YapA, in the Fungal Symbiont Epichloë festucae

Abstract: One of the central regulators of oxidative stress in Saccharomyces cerevisiae is Yap1, a bZIP transcription factor of the AP-1 family. In unstressed cells, Yap1 is reduced and cytoplasmic, but in response to oxidative stress, it becomes oxidized and accumulates in the nucleus. To date, there have been no reports on the role of AP-1-like transcription factors in symbiotic fungi. An ortholog of Yap1, named YapA, was identified in the genome of the grass symbiont Epichloë festucae and shown to complement an S. ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 84 publications
1
17
1
Order By: Relevance
“…For example and in contrast to our results, yapA deletion in symbiotic fungus Epichloë festucae causes sensitivity to H 2 O 2 and t -BOOH in conidia but not in mycelia and YapA, instead of AtfA, is required for expression of the spore-specific catalase CatA (Cartwright and Scott, 2013). Neurospora crassa mutants lacking the NapA homolog NcAp-1 were reported as showing no sensitivity to osmotic stress and only a slight sensitivity to H 2 O 2 (Takahashi et al, 2010), although recent work showed that mutants were sensitive to osmotic stress, cadmium and H 2 O 2 (Tian et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For example and in contrast to our results, yapA deletion in symbiotic fungus Epichloë festucae causes sensitivity to H 2 O 2 and t -BOOH in conidia but not in mycelia and YapA, instead of AtfA, is required for expression of the spore-specific catalase CatA (Cartwright and Scott, 2013). Neurospora crassa mutants lacking the NapA homolog NcAp-1 were reported as showing no sensitivity to osmotic stress and only a slight sensitivity to H 2 O 2 (Takahashi et al, 2010), although recent work showed that mutants were sensitive to osmotic stress, cadmium and H 2 O 2 (Tian et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that none of these peroxiredoxins was required for H 2 O 2 or menadione resistance and therefore are unnecessary for NapA activation. This is consistent with results in E. festucae , where peroxiredoxins Gpx3 (GpxA) and Tpx1 (TpxA) were not needed for YapA H 2 O 2 -induced nuclear accumulation (Cartwright and Scott, 2013). On the contrary, M. oryzae mutants lacking Gpx3 functional homolog MoHYR1 are sensitive to H 2 O 2 , fail to express several genes related to the antioxidant response and show reduced virulence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…E. festucae is an endophyte that intercellularly colonizes the aerial tissue of its perennial ryegrass host, Lolium perenne. In ΔyapA mutant strains of E. festucae, conidia were hypersensitive to H 2 O 2 while hyphae were not (Cartwright and Scott, 2013). However, unlike UmAp1, YapA was not required for plant infection.…”
Section: Biotrophs and Endophytesmentioning
confidence: 94%
“…nih.gov/Blast.cgi) (Cartwright and Scott, 2013). The corresponding gene was identified in the G. lucidum genome database G. lucidum G.260125-1 (taxid: 1077286) (GL25996-R1) (Chen et al, 2012).…”
Section: Cloning and Analysis Of The Gpx Genementioning
confidence: 99%